Поховальний обряд могильника Острів (за матеріалами розкопок 2017—2018 рр.) - Баранов, В.І.; Івакін, В.Г.; Широухов, Р.А. (Археологія і давня історія України, 2021)
Стаття присвячена загальній характеристиці
поховального обряду могильника Острів (Рокитнянський район Київської області). Вперше аналізується весь інформаційний масив археологічних даних, отриманих за перші два роки дослідження цієї
унікальної пам’ятки. Основна увага приділяється
особливостям поховального обряду та категоріям
супроводжувального інвентарю, здійснюється попередня спроба визначити час функціонування могильника, його місце та роль у контексті старожитностей Давньоруської держави. In 2017—2018 researchers of Architectural and Archaeological
Expedition (Institute of Archaeology of
Ukraine) conducted investigations in the Ostriv village
Rokytne district Kyiv region. As a result, 53 inhumation
burials of the graveyard unique for Southern Rus were
investigated. Analysis of the burial equipment allowed
us to date the graveyard to the end 10th — 11th c.
Funeral rite detected in the graveyard differs considerably
from usual Kyivan Rus burials of this period.
Vast majority of burials were oriented to the north with
small season deviations. There were individual burials
oriented to the south and to the west. Most were buried
lying on their back with outstretched limbs in variety of
wooden structures (coffins). Remains of a stone structure
have been discovered. It can be reconstructed as
the remains of an altar. Remains of funeral food were
found in burials, among them chicken bones, eggshells,
buckets for liquids and powders.
The graveyard is characterized by wide range distinctive
accompanying equipment, not typical to synchronous
Kyivan Rus graveyards, but close to funeral
rite of people living in the southern-east coast of Baltic
sea, basically the Western Baltic tribes of Curonians,
Prussians, Scalvians.
It should be noted that the funeral tradition recorded
on the Ostriv graveyard does not fit directly
into the synchronous antiquities of Eastern Europe. It
has no direct analogies among the Baltic sites known
today either. This looks a bit odd, as the grave goods
discovered at Ostriv cemetery have direct analogies
in the Western Balts monuments. The absence of cremation
burials typical to the Western Balts is still
under the question here. This situation can reflect
the restrictions of Kyiv princely Christian administration.
Possibly Ostriv cemetery illustrates Primary chronicle
reports on state activity of first Kyiv dukes, particularly
Volodymyr the Great and Yaroslav the Wise, who
straightened and pushed further the southern borders
of Kyiv Rus.